A Multi-Attribute Utility Theory-Based Ranking System for PKH Social Assistance Recipients - Rezki Kurniati; Aldi Suhandi (Program Studi Teknik Komputer, 2026)
Purpose – This study aims to design and evaluate a mobile-based decision support system for ranking prospective recipients of the Program Keluarga Harapan (PKH) in Parit Satu Api-Api Village. The system is intended to support objective, transparent, and traceable recipient selection, particularly in village-level contexts where manual selection may lead to subjectivity, delays, and limited accountability. Design/methods/approach – The system was developed using the waterfall model. Multi-Attribute Utility Theory (MAUT) was applied to calculate utility and preference values based on six criteria: household income, family dependents, social status, occupation, housing condition, and school-age children. A simulation using seven alternatives was conducted, and system functionality was evaluated through black-box testing. Findings - The system provides criteria, subcriteria, alternative, assessment, ranking, user management, and PDF reporting features. The simulation results show that alternative A1 obtained the highest preference value of 0.653, followed by A4 and A6 with equal values of 0.650. The corrected MAUT calculation produced a more consistent ranking because higher subcriteria scores represented greater socioeconomic vulnerability and higher assistance priority. The system also automates normalization, weighting, ranking, and PDF-based reporting. Research implications/limitations – The system can support faster, more systematic, and better-documented PKH recipient selection at the village level. However, this study is limited to a small simulation dataset and black-box functionality testing. Further evaluation using larger real-world data, controlled timing tests, and user acceptance assessment is required. Originality/value – This study contributes a mobile-oriented MAUT-based decision support system tailored to village officer workflows, with emphasis on calculation traceability, recipient ranking, and PDF reporting.